Mythbusters : the Counter-Cyclical Nature of Gold Prices & January as a Predictor of Market Performance for the Year - Hines, Zach; Nohelty, Eric; Porwoll, Matt; Buxton, Lauren (My University, 2011)
There are many different theories and strategies concerning the stock market. Data has been compiled to test two of these theories: The first theory looked at is one that states that market performance in the month of January can be used as a predictor for the performance of the entire year. The second theory is that gold is counter-cyclical to the broad market and is a good place to invest in a bear market. The Chippewa Valley Center for Economic Research and Development (CVCERD) collects market data on four different investment strategies and also provides an overview of overall market conditions through its Stock Market Project. In addition to testing these market hypotheses, an overview is presented of the broad stock market and the Eau Claire Basket (an index of locally represented publically traded companies).
Color poster with graphs and tables.
Keywords: Business cycles; Gold; Prices; Stock price forecasting; Investments--Decision making; Posters; Stocks--Wisconsin--Eau Claire